RAPD MARKER FOR DETERMINATION OF PHYLOGENETIC RELATIONSHIPS OF 15 CURCUMA SPECIES FROM THAILAND - Theanphong, Orawan; Thanakijcharoenpath, Witchuda; Palanuvej, Chanida; Ruangrungsi, Nijsiri; Rungsihirunrat, Kanchana (Interprofessional Journal of Health Sciences, 2023)
Curcuma, a rhizomatous herb belonging to the family Zingiberaceae, has been used as a natural food additive, cosmetic and folk medicine in Thailand. According to the similar morphology of Curcuma species, makes it difficult for species identification. In this study, Random Amplified Polymorphic DNA (RAPD) was employed for determination of the phylogenetic relationships among 15 Curcuma species from Thailand. Out of thirty random deca-arbitrary primers, only four produced clear and reproducible polymorphic bands. Twenty-two to twenty-eight products were amplified, with an average of 24.5 bands by each primer. A total of 98 bands ranging from 208 to 4136 base pairs in size were amplified, among which 39 products were found to be polymorphic. The similarity index (SI) ranged from 0.0909-0.9222. The dendrograms were constructed based on unweighted pair group method with arithmetic averages (UPGMA). The results from the cluster diagram could be divided into three major groups and the phylogenetic relationships were correlated with the morphological characteristics. In conclusion, RAPD marker was successfully for differentiating among 15 Curcuma species from Thailand and providing a simple and rapid tool for differentiation.